Dramatizing national dignity in El Lozy's trilogy - Selim, Samy (AUC Knowledge Fountain, 2010)
Mahmoud El Lozy's trilogy, We That Are Young, consists of three plays: Bay the Moon, And Then Went Down to the Ship, and Us and Them (a widely circulating unpublished typescript written in 1998-2005 that has been performed and directed by the author or/and directed as staged reading in Cairo privately-- or by invitation--as well as publicly in New York). This thesis analyses how El Lozy dramatizes the concept of national dignity from the Arab and Egyptian perspectives. The trilogy is contextualized using the writings of Frantz Fanon, Edward Said, and Galal Amin. El Lozy's status as a dramatist and critic is presented. The close reading of three crucial scenes demonstrates how Egyptian/Arab independence is threatened through co-option and the manner with which it is defended in the plays. The three scenes are also used to explore the intertwining themes of national honor, the neo-colonialist tendencies of the West, the Western use of media to undermine Arab dignity and distort the Arab image, and the overall arc of deterioration exhibited by the scenes. The conclusion is that in spite of all attempts to undermine Arab and national integrity, El Lozy's trilogy is optimistic because neither of the protagonists succumbs to co-option.